Two sibling green lacewing species, Chrysopa pallens and Chrysopa gibeauxi (Insecta: Neuroptera: Chrysopidae) in Slovenia and western Balkan countries - Devetak, Dušan (Annales. Series historia naturalis, 2015)
Green lacewing species, Chrysopa gibeauxi (Leraut, 1989), was recently reinstated as a valid species, and closely related to Chrysopa pallens (Rambur, 1838). Evaluation of morphological diagnostic characters of the two sibling species justified the separation of the two species. After re-examination the available insect material from Slovenia and western Balkan countries it was revealed that Chrysopa pallens is widely distributed in the area, whilst Chrysopa gibeauxi is a rare green lacewing, recorded in Slovenia, Croatia and Serbia (Kosovo). The distribution of the latter species is for sure larger than appearing. Some details concerning morphology and habitat of the species are provided. The erroneous citations given for Slovenia, assigned now to Chrysopa gibeauxi, are corrected.
Keywords: Balkan; Balkans; Neuroptera; nove najdbe; Slovenia; Slovenija; tenčičarice